MicroRNAs and rs1803274 SNP-based BuChe downregulation are associated with metabolic syndrome through ghrelin hydrolysis and expression quantitative trait loci regulation in PD patients - Chevalier, Guenson; Udovin, Lucas; Otero-Losada, Matilde; Bordet, Sofia; Perez-Lloret, Santiago; Capani, Francisco (Frontiers in Molecular Neuroscience, 2025)
IntroductionMetabolic syndrome (MetS) and Parkinson’s disease (PD) share common pathophysiological and molecular impairments related to high PD incidence in MetS patients. In this study, we searched for independently MetS-associated single-nucleotide polymorphism variants (SNVs) in PD patients and aimed to explain the molecular mechanism involved.MethodsWe included 423 PD patients diagnosed by positron emission tomography (PET). A logistic regression model, the chi-squared analysis, and Fisher’s exact test were applied to additive, dominant, and recessive genetic models of data obtained from the Parkinson’s Progression Marker Initiative (PPMI) database. MicroRNA Quantitative trait Loci (MirQTL) analysis and microRNA binding to 5′/3′- untranslated regions (UTR) and conding sequence (CDS) region gene prediction analysis were performed. Expression quantitative trait loci mapping (eQTL) and gene prioritization using weighted co-expression network analysis were used to evaluate the molecular mechanisms. Chromosomal loci that explain variance in expression traits are referred to as eQTLs.ResultsThe SNV variant rs1803274 was associated with MetS, increased cardiovascular risk, and altered butyrylcholinesterase levels. Eleven microRNAs binding to the BuChe 3′/‘5-UTR and CDS region downregulated its expression. The rs1803274 variant was significantly enriched for neurotransmitter clearance, ghrelin secretion and deacylation, phosphatidylcholine synthesis, glycerophospholipid and lipid metabolism, and synaptic transmission. Forty-six eQTL proteins were associated with the SNV rs1803274. Thirteen of these were prioritized as potential therapeutic targets in a principal component analysis based on node degree parameters, betweenness centrality, and closeness centrality.Conclusion and interpretationThe SNV variant rs1803274 was associated with both MetS and PD and downregulated the expression of BuChe, which is involved in ghrelin hydrolysis. This variant was associated with several MetS-related eQTLs proteins or their components.